2022
DOI: 10.21203/rs.3.rs-1826691/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of heat shock proteins in hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Background: Several studies were conducted to explore the clinicopathological characteristics and prognostic value of heat shock proteins in hepatocellular carcinoma (HCC). However, the results remain controversial. To address this gap, we conducted a systematic review and meta-analysis.Methods: The eligible literature was obtained from PubMed, Cochrane library, Web of science, Embase, Chinese National Knowledge Infrastructure and Wan Fang databases. We used the odds ratio (OR) and hazard ratio (HR) as the sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Elevated levels of HSP expression have been observed in various human malignancies, including HCC, colorectal cancer, cervical cancer, breast cancer, prostate cancer, and lung cancer [19]. Several studies have demonstrated that HSPs are potential biomarkers for cancer diagnosis and prognosis [19][20][21]. Recently, a few studies estimated the diagnostic value of HSPs for detecting HCC, but the diagnostic accuracies are inconsistent and even conflicting [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of HSP expression have been observed in various human malignancies, including HCC, colorectal cancer, cervical cancer, breast cancer, prostate cancer, and lung cancer [19]. Several studies have demonstrated that HSPs are potential biomarkers for cancer diagnosis and prognosis [19][20][21]. Recently, a few studies estimated the diagnostic value of HSPs for detecting HCC, but the diagnostic accuracies are inconsistent and even conflicting [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%